Identification and Antibacterial Activity of Propionibacterium Acnes of Ethyl P-Methoxy Cinnamate Isolated from Kaempferia Galanga Linn - Usi Hikmah Utami; Ratna Djami; Deni Rahmat; Sofa Fajriah; Greesty Finotory Swandiny (International Journal Labs, 2023)
Kaempferia galanga Linn is a typical Indonesian plant that contains the compound Ethyl P-Methoxy Sinnamate which has antibacterial activity. Acne is a common skin condition characterized by inflammation of the hair follicles and oil glands in the skin. The most effective acne treatment is the use of antibiotics. This research is an experimental study and aims to identify galangal rhizome isolates (Kaemperia galangan L) obtained from N-Hexane extract. using Thin Layer Chromatography (TLC) and Densitometry TLC as well as testing the antibacterial activity of the acne-causing Propionibacterium acnes ATCC 6919 using Complete Tool Design (RAL) with SPSS analysis, confidence level (p<0.05) and continued with the ANOVA test using the disc diffusion and liquid dilution methods for MIC. On In Vitro test Kaempferia galanga Linn contains antibacterial compounds that cause acne, namely Ethyl P-Methoxy Sinnamate with medium-strong strength at a concentration of 0.6%; 1.2%, and 2.4% with an inhibition zone of 8.70 mm; 10,10 mm and 11.70 mm. The clear zone for Clindamycin is 27.30 mm. Ethyl P-Methoxy Cinnamate (EPMS) isolated from Kaempferia galanga Linn N-Hexane extract Kaempferia galanga Linn has a concentration of 1.572 g/mL and has activity against Propionibacterium acnes bacteria at a concentration of 0.6%; 1.2% and 2.4%